The link between Permeable Interlocking Concrete Pavement (PICP) design and nutrient removal - Liu, Kimberly (Department of Civil Engineering, 2021)
Urbanisation, associated with the construction of ‘hard' impermeable surfaces such as roofs and roads, results in increased stormwater runoff peak flows and volumes and their associated pollutants into downstream receiving waters compared with the pre-development state unless mitigated through Sustainable Drainage Systems (SuDS). Permeable Pavement Systems (PPS), one of the source control options in SuDS suite, are able to control stormwater runoff and reduce the discharge of pollutants (Armitage et al., 2013). Urban runoff typically includes sediment, trash, heavy metals, organic matter, hydrocarbons and nutrients. PPS are able to remove a sizeable proportion of these through sedimentation, filtration, adsorption and biodegradation. The most commonly used PPS in South Africa are Permeable Interlocking Concrete Pavements (PICP) which comprise concrete pavers laid on selected stone layer works with surface infiltration enabled by the presence of carefully designed openings between the pavers filled with fine stone. The treatment performance of PICP systems appear to depend on various factors such as: the layout of the pavers; the size and condition of the stone aggregates; the presence and location of any geotextiles; the type of outlet; and the time period between rain events. While some research on the treatment of stormwater by PICP has been published, not enough is known about the relative performance of different PICP designs. This dissertation describes an investigation on the performance of 10 different PICP systems constructed in the civil engineering laboratory at the University of Cape Town (UCT) for the treatment of various nutrients (ammonia-nitrogen, orthophosphate-phosphorus and nitrate-nitrogen) commonly found in stormwater runoff. Ten experimental cells each housing a different permeable pavement design were constructed in the NEB laboratory at the UCT. Infiltration tests (ASTM C1781) were first conducted to test the hydrological performance of each of the PICP cell. This was followed by ‘clean water' tests to establish the ‘base-line' pollutant values prior to the additional of any pollutants. Finally, typical Cape Town rainfall events were simulated using a synthetic stormwater mixture containing representative nutrients concentrations to test the treatment efficacy for each of the permeable pavement systems over the period of two years with intermittent dry and wet periods. The influent and effluent from all ten experimental cells were periodically collected and analyzed for pH, temperature, electrical conductivity and the effluent concentrations of ammonia-nitrogen, orthophosphate-phosphorus, nitrite-nitrogen and nitratenitrogen. It was found that there is a reduction of ammonia-nitrogen for all experimental cells ranged from 27.5% to 78.7% compared with the average of 63.7% removal rate from other studies. However, the reduction in the ammonia-nitrogen effluent concentrations may not be true removal as the ammonia-nitrogen may have been converted into nitrite-nitrogen or nitrate-nitrogen through the nitrification process. It was also found that: the cells with geotextiles had higher ammonia-nitrogen reduction than those cells without; the cells with washed aggregates had higher ammonia-nitrogen reduction than those cells with unwashed aggregates; and the cell with a raised outlet (creating a ‘sump' in the underlying stone aggregate) had the highest ammonia- nitrogen reduction of all. The orthophosphate-phosphorus effluent concentrations ranged from 37% orthophosphate-phosphorus addition to 11% orthophosphate-phosphorus reduction compared with the average of 47.7% removal rate of orthophosphate-phosphorusin other studies. The presence of geotextile resulted in higher orthophosphate-phosphorus removal efficiencies than those cells without; the cells with washed aggregates had higher orthophosphate-phosphorus removal efficiency than those cells with unwashed aggregates. The cell with an elevated outlet (sump) had the least orthophosphate-phosphorus removal efficiency. In addition, it was found that all the experimental cells added significant quantities of nitrates having nitrate-nitrogen addition ranging from 160% to 2580% which may be due to the nitrification process of ammonianitrogen (NH3) to nitrate-nitrogen (NO3 - ). The cell with the raised outlet had the highest nitratenitrogen addition which can be explained by its highest ammonia-nitrogen removal efficiency through the nitrification process. It was also found that the presence of geotextile has a negative impact on the nitrate-nitrogen removal efficiencies, possibly because geotextiles provide a habitat for the microbes that encourage nitrification. The nitrification process, promoting the reduction in ammonia-nitrogen effluent concentrations and the increase in nitrate-nitrogen effluent concentrations occurs when the pH is within the optimum range of 7.6-8.8 for growth of nitrifying bacteria, Lower pH results in higher nitrate-nitrogen concentrations. It was also found that the electrical conductivity – a measure of ionic strength – strongly depends on the length of the periods between rainfall ‘seasons'; it decreases rapidly during wet periods and increases during dry periods. A field testing was also carried out on the New Engineering Building (NEB) parking lot at the UCT to confirm the true treatment performance of PPS. The results show the PICP are efficiently removing TSS, ammonia-nitrogen and orthophosphate-phosphorus. The PICP with geotextile was found to have positive impact on TSS, ammonia-nitrogen and orthophosphatephosphorus removal than the one without. It was also found the presence of geotextile has negative impact on nitrate-nitrogen removal, with lower pH resulting in higher nitrate-nitrogen concentrations which aggress the previous laboratory findings.